ASPEK SOSIAL BUDAYA MASYARAKAT MAKASSAR PADA NOVEL NATISHAKARYA KHRISNA PABICHARA - Arifa Ainun Rondiyah; Nugraheni Eko Wardani; Kundharu Saddhono (Kandai, 2017)
Cultural social in Makassar society has an impact to life point of view and orientation to interact each other. This study is to answer the problem about how is the cultural effect to society’s life in Makassar. This research aims to describe and explain the connection between literature and society relating cultural social aspect of Makassar society in Novel by Khrisna Pabichara. Data collection is done by content analysis technique. The data was analyzed with qualitave method by using literature sociology teory. Data resource of this research is Natisha novel text quote. Analysis result showed about five cultural aspects influencing Makassar society. Sirik is a principal form and perspective of Makassar society. Silariang is marriage tradition violation done by a couple to elope. Social class of Makassar society has an important role in social life. Greetings, Makassar persons greet depend on their social class. Makassar society has literature which is called lontarak with lontar leaf media.